Epidemiology of benign breast lumps, is it changing: a prospective study - Kumar, Navin; Prasad, Janardan (International Surgery Journal, 2019)
Background: There are wide range of benign breast diseases reported from India. Breast lumps are one of the commonest presentations. Although most of the breast lumps are benign but patient become anxious due to fear of malignancy. Due to this, there is an increase in the use of screening mammography and the fine needle aspiration cytology (FNAC) or core needle biopsy (CNB), most of which yield benign findings. This study is aimed to evaluate the incidence of different types of benign breast lumps in respect to age, size, side and site, relation with parity and use of oral contraceptive pills and analyses of this result in relation with the past and recent study on benign breast diseases. Methods: This study was conducted at Rajendra Institute of Medical Sciences, Ranchi (India) over a period of one and half years. Inclusion criteria was the cases with palpable breast lumps which were reported benign on either FNAC or CNB and exclusion criteria was the cases with breast malignancy and inflammatory breast lumps. Results: Most common benign breast lump (BBL) was fibroadenoma followed by fibrocystic disease of breast. Fibroadenoma was mainly presented with lump only whereas fibrocystic diseases of breast presented with lump and pain. Most of the BBL was found in nullipara and OCP non-users. Conclusions: Epidemiology of BBL is still the same when analyzed with past and recent study on the benign breast diseases. Triple assessment remains the key in the evaluation of breast lumps.